Prognostic markers in operated non-small cell lung cancer patients (Annals of Medical Research, 2023)
Aim: The overall survival (OS) of operable lung cancer patients is directly related to clinicopathological features and some laboratory parameters. In this study, we aimed to examine the factors affecting the survival of the operated patients.Materials and Methods: In our study, we retrospectively analyzed 202 operated-on patients diagnosed with lung carcinoma who were in stages I–IIIA at the time of diagnosis. The clinico-pathological features and some laboratory parameters of the patients included in our study were retrospectively analyzed. The effects of those parameters on the overall survival of the patients and their disease-free survival (DFS) have been investigated.Results: The age of the patient at the time of diagnosis and the presence of lymphovascular invasion (LVI) were found to be statistically significant in terms of OS (p